Assessing Endothelial Function in Normotensive Overweight Adolescent Using Dundee Step Test (Faculty of Medicine Universitas Indonesia, 2010)
Aim Normotensive overweight adolescents may have endothelial dysfunction which is not clinically detected in a routine clinical examination. The purpose of this study was to detect endothelial dysfunction in normotensive overweight using Dundee step test. Methods Sixty two subjects consist of 31 normoweight and 31 overweight group participated in this study. Blood pressure measurement was taken at rest and after 3 minutes Dundee step test. Hyper-responder was defined if systolic blood pressure reach 180 mmHg or more after 3 minutes exercise. Results Mann-Whitney test showed that overweight subjects had significantly higher resting systolic blood pressure, post exercise blood pressure anf magnitude of SBP change (Δ SBP) compared to control subjects (116.5 vs 112.8; 163.8 vs 142.7 vs; and 47.3 vs 29.9; P<0.05). Twenty six percent of overweight was diagnosed as hyper-responder. Conclusion There was significant association between overweight and ExSBP indicating endothelial dysfunction in normotensive overweight adolescents. (Med J Indones 2010; 19:52-6) Keywords: adolescent, Dundee step test, endothelial dysfunction, overweight, systolic blood pressure